PELATIHAN MODEL PEMBELAJARAN QUANTUM DI SEKOLAH DASAR PADA GURU-GURU SD MUHAMMADIYAH 3 SURAKARTA TRAINING ON QUANTUM LEARNING MODEL FOR THE TEACHERS OF MUHAMMADIYAH 3 SURAKARTA ELEMENTARY SCHOOL - Muhklis Mustofa, Oktiana Handini & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
This community service is Training on Quantum Learning Model for the teachers of Muhammadiyah 3 Surakarta Elementary School. It aims to increase learning quality and interactive learning process be enjoying class. Quantum learning helps effectively students to create large chance to see and build many concepts in learning. The concept of bring their world to our world and flow our world to their world be interactive, active and enjoy. By giving interactive chances make students understand more about complex problems in surrounding become correleted holistic paradigm. Quantum Learning Model applies learning syntaxes Grow â Experience â Name - Demonstrate â Repeate â Celebrate. (TANTUR ; Tumbuhkan, Alami, Namai, Demonstrasikan, Ulang, Rayakan). The result of this community service is hoping teacher can be a leader of oschestra in classroom to conduct students who have ability to identify, to collect, to evaluate and to solve problems in learning process.Keyword : Quantum Learning Model